Publish, manage, and consume services using ArcGIS server. - Nelson, Steph A.; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"ArcGIS Server provides a backbone for web maps and applications. Users can publish data from shapefiles, files, and enterprise geodatabases to allow for customized display and access in web maps and applications. In the first section of this course, viewers will learn how to publish dynamic and cached map services, an editable feature service, a feature service with a related table, a WMS and WFS, and a KML service. In the second section of this course, viewers will learn how to access and view services via the ArcGIS REST services directory, Server Manager, and ArcCatalog. In the last section of this course, viewers will learn how to use other mapping APIs to add ArcGIS REST services to a web map."--Resource description page.
Title from resource description page (Safari, viewed October 16, 2017).
Presenter, Steph A. Nelson.
Keywords: ArcGIS; Geographic information systems -- Programming; Geographic information systems; Spatial data infrastructures; Electronic books